Complications in surgery - Mulholland, Michael W.; Doherty, Gerard M. (Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"Complications in Surgery is organized to cover both the broad concepts of surgical care and the complications relevant to operations on specific organs. Surgical epidemiology, operative technique, and disease pathophysiology are each essential in contemporary surgical practice; each is emphasized in this new textbook"--Provided by publisher.